1998
DOI: 10.1007/978-3-7091-9459-1_3
|View full text |Cite
|
Sign up to set email alerts
|

A Decision Method for Elementary Algebra and Geometry

Abstract: Prepared for publication with the assistance of J. C. C. McKinsey This work has a long history. Its main results were found in 1930 and first mentioned in print a year later. It took nine years, however, before the material in its full development was prepared for publication. In fact, a monograph embodying those results was scheduled to appear in 1939 under the title The completeness of elementary algebm and geometry in the collection Actualites scientifiques et industrielles, Hermann & Cie, Paris. As a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
484
0
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 665 publications
(487 citation statements)
references
References 0 publications
0
484
0
3
Order By: Relevance
“…Even though decision methods exist for (R, +, −, ×, <, 0, 1) [22], it is not known if the theory of R exp is decidable, although in [16] it was shown that it would be a consequence of Schanuel's conjecture in number theory. The results we obtained in this paper suggest how to find some restricted classes of vector fields for which the algorithm is constructive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though decision methods exist for (R, +, −, ×, <, 0, 1) [22], it is not known if the theory of R exp is decidable, although in [16] it was shown that it would be a consequence of Schanuel's conjecture in number theory. The results we obtained in this paper suggest how to find some restricted classes of vector fields for which the algorithm is constructive.…”
Section: Discussionmentioning
confidence: 99%
“…Tarski [22] was interested in the extension of the theory of the real numbers by the exponential function, (R, +, −, ×, <, 0, 1, exp) (i.e., there is an additional symbol in the language for the exponential function). We denote this structure by R exp .…”
Section: Definition 9 the Theory Of L Is O-minimal ("Order Minimal")mentioning
confidence: 99%
“…While the finiteness and uniformity properties of PL-geometry and tropical geometry are easy enough to demonstrate directly, the o-minimality of this underlying structure puts these results into context. That (R, +, ×, <, 0, 1), the set of real numbers considered as an ordered field, is o-minimal is a consequence of Tarski's theorem on elementary geometry (first proved in 1929, but only published in 1948 [41]) and is the basis of semi-algebraic geometry.…”
Section: Thomas Scanlonmentioning
confidence: 99%
“…Tarski [10] showed that OF(R) is decidable, i.e., there is a computational procedure that, given any R-sentence φ, decides whether φ belongs to OF(R). The decision procedure is based on the elimination of the quantifiers.…”
Section: Decidability and Quantifier Eliminationmentioning
confidence: 99%
“…The main computational tool for symbolic set manipulation in this context is quantifier elimination. Since quantifier elimination is possible for the theory of reals with addition and multiplication [10,15], we either find or transform subclasses of o-minimal hybrid systems which are definable in this theory. This immediately leads to new decidability results.…”
Section: Introductionmentioning
confidence: 99%